The suitability of Sinjar and Pila spi rocks for building and as railway ballast stone for the Bazian anticline fold in the Sulaymaniyah governorate - Maher Najm Abdullah; Mohammed Rashid Abood; Amera Ismael Hussain (Tikrit Journal of Pure Science, 2022)
The research aims to find the suitability of limestone rocks belonging to the Sinjar and Pila Spi Formations in the southwestern part of the Bazian fold in Sulaymaniyah Governorate for building purposes and as a railway ballast stone by conducting some important geotechnical laboratory tests and comparing them with the required standard specifications for building stones and railway ballast stone. Through these tests, it was found that the values ​​of the dry density of the studied samples ranged from (1.87-2.31) (g/cm³), while the values ​​of the water absorption coefficient ranged from (1.84-9.87)%, and the specific weight values ​​ranged from (2.16-2.25), while the values ​​of The unconfined compressive strength ranged between (31-55) MPa in its natural state, and the Flexural strength values ​​ranged from (5.5-11.9) MPa, and the mechanical abrasion percentage values ​​ranged between (24.4%-61.6%). After comparing the values of these properties with the specifications required for building stones and the specifications required for railway ballast stones, it was found that the limestone rocks in the study area are suitable for building purposes, but they are not valid as a railway ballast stone.